أثر أساليب معاملة الوالدين للأطفال في تشكيل سلوكهم تجاه الآخرين في ضوء الرؤية الإسلامية : The Influence of Parent’s Methods in Dealing with Their Children in Forming Behavior Towards Others in light of Islamic Perspective - Abdulrahim Hamei, Amna Salh; Musal Kassim, Sayyid Buhar; Yusof, Muhammed (Journal Al-Muqaddimah, 2023)
The methods of parents in raising their children and treating them since childhood have profound effects on children’s personalities and behaviours in various aspects of life, including the way they deal with others. There is no doubt that this matter is of great importance, as man is a social being by nature and he cannot live isolated from people, but his interests require that he coexist with them. Hence, the way he deals with people will have a great impact on his success in his life and his ability to adapt to people and achieve his legitimate goals and desires to enjoy a good and stable life away from problems and psychological pressures. So, the identification of the methods of parents’ treatment to their children and distinguish the negative from the positive of them is of great importance, and this is what is addressed in this paper to recognize these methods and to identify the opinions of psychologists, sociologists, and educationists on that in the light of the balanced and directed Islamic vision.